Archival science between social and natural sciences - Klasinc, Peter Pavel (Atlanti +, 2024)
Purpose: The purpose of this paper is to present research on classification of archival science among social science, but at the same time we want to find an-swers to whether archival science can also be classified among natural sciences.Method/approach: The results of this paper are based on several methods. The first one is the comparative method of the study programs and profiles of the graduate students at the University of Ljubljana in correlation to the types of archival material which those specialists produced. Another method used in the paper is the method of studying different sources like websites, literature etc. including the experiential method. Results: This paper presents the results of this research, which will place all three sciences in clear starting points related to archival science, archivistics and archival theory and practice. Conclusion: The fact is that archival science is gaining ground as an independ-ent, academic, multidisciplinary and interdisciplinary science; therefore, we must place it within clear starting points, which are typical for both social and natural sciences.
Keywords: archival material; archival science; arhivska znanost; arhivsko gradivo; družboslovje; naravoslovje; natural science; social science